Loss of wood resources and biodiversity in Ukrainian forests - Калашніков, А. О.; Жежкун, І. М.; Торосов, А. С. (Forestry and Forest Melioration, 2024)
Introduction Ukraine’s forests perform ecological and social functions and are also a source of various renewable natural resources and wood. The use of forest resource potential should ensure the effective management of forested areas for wood production. In recent decades, combating deforestation and assessing forest biodiversity have gained significant importance, particularly in the context of climate change and increasing socio-economic pressures. The ongoing war in Ukraine, which began in 2022, has further exacerbated these challenges, posing severe threats to forest ecosystems and conservation efforts. The war’s negative impact on Ukraine’s forestry sector is evident in the declining share of forest-related revenue in the national GDP, workforce reductions, and a shortage of skilled personnel. However, tax revenues and payments paid to budgets of all levels by the forestry sector in 2023 indicate its significant contribution to the country’s economy. A partial stabilization of industrial activity was observed in 2023, particularly in the sectors related to wood processing, following the initial disruptions caused by the Russian invasion. Materials and Methods The study used quantitative statistical methods, including data grouping, comparative analysis, tabular and graphical modeling, and economic synthesis. The input information for the analysis was open-source information from the Food and Agriculture Organization of the United Nations (FAO), the State Statistics Service of Ukraine, SE “Forests of Ukraine”, the State Agency of Forest Resources of Ukraine (SAFRU), as well as legislative documents and scientific publications. A comprehensive assessment of the decline in wood harvesting in 2022 as a result of military actions was conducted by estimating losses in forest resource potential (due to the areas of temporarily occupied forest-covered territories). Results The study examined annual net forest area change rates from 2000 to 2020. By 2022, direct economic losses in the forestry sector of Ukraine from the reduced harvesting volumes due to the loss of forest resource potential under the influence of military actions were estimated at 1576.8 thousand m3 of wood, amounting to almost UAH 2.56 billion in prices of an impersonal cubic meter of harvested wood of SAFRU enterprises. Forest fires affected 15.8 thousand hectares in 2022 and 51.0 thousand hectares in 2023 in government-controlled areas, causing economic losses of UAH 302.4 million and UAH 2.05 billion, respectively. The total damage to Ukraine’s Nature Reserve Fund is estimated at UAH 628.25 billion, with 80.6% of losses attributed to the destruction and degradation of trees and vegetation. The interrelationship of ecological, social and economic risks from the loss of forest biodiversity has been studied. The Russian invasion had a catastrophic impact on Ukraine’s socio-economic stability, significantly altering development trends. Its negative effects on forestry and related industries have disrupted the stability of Ukraine’s wood market. Over two years of military operations, total damage to the forest sector is estimated at UAH 20 billion (USD 540 million), with UAH 420 million (USD 11.5 million) in destroyed equipment and UAH 1.2 billion (USD 32.5 million) in damaged real estate. Given the intensity of hostilities and the challenges in controlling forest fires near front-line areas, further deterioration in forest conditions and increased economic losses in the forestry sector are anticipated due to declining resource availability. Conclusions The above trends in Ukraine’s forest sector will be observed over the next few years, given that military operations in the country are still ongoing. A certain period will be required to restore and develop the forest resource and production potential of the forestry and woodworking industries, as well as the state economy, after the end of military operations in the country. The preservation of Ukraine’s forest resource potential and biodiversity remains a pressing issue, further complicated by ongoing large-scale military operations. The success of restoring and developing the forest resource potential and plant biodiversity of Ukraine, which was lost or damaged due to military operations in 2022-2024, will largely depend on improvements in national environmental legislation, as well as securing investments from state resources, private enterprises, international donors, and potential reparations from the aggressor country. Successful restoration and conservation will require a multi-faceted approach, integrating ecological, economic, and legal measures to mitigate long-term damage. 3 Figs., 3 Tables, 17 Refs.